PREVENTION AND COMMUNICATION IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2012)
This article introduces a special “Management of prevention and communication” which ispresented as an integrative company and leadership culture. The program is based on preventionmanagement and communicative competence as a staff training. Further it includes a teaching,learning and company internal practical orientation and transfer of interdisciplinary-socialintegrativeelements like movement (exercise), nutrition, relaxation as well as communication andstress management. The program's goal is to make a continuous strategy of coping with life andlivelihood with key qualifications for workers, employees and managerial staff available.
Keywords: prevention; communication; stress